Remembering Nature in Climate Change: Re-thinking Climate Science and Climate Communication through Critical Theory. : RCC Perspectives: Transformations in Environment and Society 2019, no. 4: Communicating the Climate: From Knowing Change to Changing Knowledge: Remembering Nature in Climate Change: Re-thinking Climate Science and Climate Communication through Critical Theory. - Born, Dorothea (Rachel Carson Center for Environment and Society, Munich, Germany, 2019)
In this article, Born draws on Critical Theory to chart a course between Walsh’s call to decenter science in climate communication because of its entanglements with power, and Oomen’s defense of science as a common ground and his warning against relativism. Born argues that we first need to make explicit the ways that science is bound up with capitalist production, and understand that the domination of nature is linked to the domination of humans’ inner nature. She illustrates this with a discussion of iconic images of polar bears, often used to communicate climate change in popular science magazines. These images obscure both the effects of climate change on human populations living in the Arctic and its roots in the burning of fossil fuels to support Western lifestyles.